Strategic thinking - Bruce, Andy; Langdon, Ken (DK essential, 2000)
Helps to learn how to define, develop, and implement a dynamic business strategy. This guide shows you how to plan short- and long-term objectives, how to put together the right team for the right job, how to communicate your vision, and how to maintain a flexible approach by monitoring past performance and predicting future trends.